Caste association and political process in Gujarat : a study of Gujarat Kshatriya Sabha - Shah, Ghanshyam (Publications - Centre for Regional Development Studies, Surat ;, 1975)
Study of the role of Kshatriya Sabha, a caste association of Hindus in politics in Gujarat.